2011
DOI: 10.1038/cr.2011.40
|View full text |Cite
|
Sign up to set email alerts
|

The human TTAGGG repeat factors 1 and 2 bind to a subset of interstitial telomeric sequences and satellite repeats

Abstract: The study of the proteins that bind to telomeric DNA in mammals has provided a deep understanding of the mechanisms involved in chromosome-end protection. However, very little is known on the binding of these proteins to nontelomeric DNA sequences. The TTAGGG DNA repeat proteins 1 and 2 (TRF1 and TRF2) bind to mammalian telomeres as part of the shelterin complex and are essential for maintaining chromosome end stability. In this study, we combined chromatin immunoprecipitation with high-throughput sequencing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
150
2
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(169 citation statements)
references
References 42 publications
15
150
2
2
Order By: Relevance
“…Given the reported role of TRF1 and TRF2 in the control of replication fork progression through telomeric chromatin (Sfeir et al 2009;Ye et al 2010), it is possible that these shelterin components play a similar role in other regions of DNA that are difficult to replicate, such as those packaged as heterochromatin. Gene ontology data (Simonet et al 2011) suggested that a large subset of TRF binding sites may have functional relevance since they occur more frequently within or in close proximity to genes, which agrees with results from Martinez et al, since TRF sites are frequently located in intronic regions or distant from promoters (Simonet et al 2011). Thus, TRF1 and TRF2 possibly regulate gene expression through looping mechanisms or by modifying the chromatin landscape.…”
Section: Extratelomeric Role Of Shelterin Complex Proteins Rap1 Trf1supporting
confidence: 79%
See 3 more Smart Citations
“…Given the reported role of TRF1 and TRF2 in the control of replication fork progression through telomeric chromatin (Sfeir et al 2009;Ye et al 2010), it is possible that these shelterin components play a similar role in other regions of DNA that are difficult to replicate, such as those packaged as heterochromatin. Gene ontology data (Simonet et al 2011) suggested that a large subset of TRF binding sites may have functional relevance since they occur more frequently within or in close proximity to genes, which agrees with results from Martinez et al, since TRF sites are frequently located in intronic regions or distant from promoters (Simonet et al 2011). Thus, TRF1 and TRF2 possibly regulate gene expression through looping mechanisms or by modifying the chromatin landscape.…”
Section: Extratelomeric Role Of Shelterin Complex Proteins Rap1 Trf1supporting
confidence: 79%
“…It should be noted that this Rap1 localization to various sites was not in response to any cellular stress. However, these data are slightly divergent from two subsequent reports also analyzed binding of telomeric proteins to extra-telomeric chromosomal sites by ChIP-seq (Simonet et al 2011;Yang et al 2011). …”
Section: Extratelomeric Role Of Shelterin Complex Proteins Rap1 Trf1contrasting
confidence: 53%
See 2 more Smart Citations
“…S-ITSs are believed to represent insertions of telomeric repeats that occur during the repair of double-stranded DNA breaks (5). A subset of s-ITSs in the human genome is bound by the shelterin proteins Rap1, TRF1, and TRF2 (6). In primates and rodents, s-ITSs colocalize with some of the chromosomal fragile sites (7,8) and map to chromosome breakpoints in cancer cells (9).…”
mentioning
confidence: 99%